The Implementation of Differentiated Learning to Foster the 4C Skills in Students in Islamic Education (PAI) Subjects - Khotimah, Siti; Saihan, Saihan; Usriyah, Lailatul (EDUTEC : Journal of Education And Technology, 2025)
Differentiated learning is an instructional approach designed to accommodate the diverse abilities, interests, and learning needs of students. This study explores the implementation of differentiated learning to foster 4C (Critical Thinking, Creativity, Collaboration, and Communication) skills in Grade X students during Islamic Education (PAI) lessons at SMK Plus Nurul Ulum Kemungsari Lor Panti Jember. The research specifically examines three aspects: the activities involved in differentiated learning, its relevance in fostering 4C skills, and the outcomes achieved through its application. This qualitative descriptive study employed observation, interviews, and documentation as data collection methods. Data were analyzed using Miles, Huberman, and Saldana’s interactive model, which includes data condensation, data display, and conclusion drawing. Data condensation involved selecting, focusing, simplifying, abstracting, and transforming the collected information. The credibility of the findings was ensured through triangulation of techniques and sources. The findings demonstrate that differentiated learning effectively supports the development of 4C skills in students by tailoring the teaching process to their unique needs. This approach not only enhances students’ engagement and learning outcomes but also highlights its relevance as a pedagogical strategy for Islamic Education.